Species-specific difference of CO₂ emissions in mangroves: coupling sediment physicochemistry and microbial communities - He, Ziying; Zhuang, Xueyin; Liang, Jin; Peng, Yisheng; Sun, Huaye; Yin, Zhushi; Xia, Meng; Zhao, Lili; Hu, Bowen; Qu, Ming; Zhu, Weidong (Frontiers in Microbiology, 2025)
Mangrove ecosystems function simultaneously as carbon sinks and carbon sources. While their contribution to biomass accumulation and long-term carbon sequestration have been extensively studied, the mechanisms driving carbon emissions, particularly those mediated by tree species and microbial communities, remain poorly understood. In this study, we investigated Kandelia obovate (KO), Sonneratia apetala (SA), and an adjacent mudflat in the Hanjiang River Estuary, southern China, to evaluate seasonal changes in sediment physicochemistry, microbial community structure, and CO₂ fluxes, and to evaluate the influence of vegetation on carbon emissions. This research shows that mangrove colonization significantly altered sediment conditions, with K. obovata exhibiting higher salinity, water content, and total carbon concentration than S. apetala. Sediment CO₂ fluxes were consistently greater in mangrove habitats than in mudflats and displayed clear seasonal variation. In summer, sediment CO₂ fluxes in S. apetala and K. obovata were 4.3- and 2.5-fold higher than in winter, respectively. Concurrently, root respiration intensified in S. apetala during summer, whereas K. obovata root respiration remained stable across seasons. Microbial communities were dominated by Proteobacteria and Chloroflexi across sites, however, their network structures differed. S. apetala supported tighter microbial interactions, while K. obovata exhibited higher modularity and functional specialization. Additionally, partial least squares structural equation modeling revealed that sediment physicochemical properties strongly constrained microbial diversity and regulated CO₂ flux both directly and indirectly. These findings highlight the importance of sediment and root respiration in mangrove carbon cycling and demonstrate how species identity modulates CO₂ fluxes by shaping the interactions between sediment conditions and microbial communities.